Single crystal structure, self-assembled nano-structure and semiconductor properties of a sandwich-type mixed (phthalocyaninato)(porphyrinato) europium triple-decker complex. (April 2015) - Lu, Jitao; Meng, Qingguo; Zhang, Liangliang; Liu, Yitong; Liu, Wenjie; Zhang, Xiaomei
Abstract: Sandwich-type (phthalocyaninato)(porphyrinato) europium triple-decker complex with butyloxy substituents at the peripheral-positions of the two phthalocyanine ligands in the triple-decker molecules Eu2 [Pc(β-OC4 H9 )8 ]2 (TClPP) (1 ) has been designed, synthesized, and characterized. Their self-assembly properties and in particular nano-structures formed have also been systematically investigated in a confirmed manner due to the available single crystal structure. Investigation reveals that introduction of butyloxy substituents at the peripheral-positions of the phthalocyanine ligands in the triple-decker molecule induces additional van der Waals interactions between neighboring triple-decker molecules. This in combination with the intermolecular π–π interaction result in the formation of one-dimensional nanostructures with rod shaped morphology. In addition, current–voltage ( I–V ) measurement result indicates good semiconductor feature of the nanorods with the conductivity of 2.2 × 10 −5 Sm −1 . Graphical abstract: The self-assembly properties of sandwich-type (phthalocyaninato)( porphyrinato) europium triple-decker complex and in particular nano-structures formed have been systematically investigated in a confirmed manner due to the available single crystal and X-ray diffraction analysis. Highlights: Triple-decker complex Eu2 [Pc(β-OC4 H9 )8 ]2 (TClPP) was synthesized. Self-assembly properties were studied in a confirmed manner. Nanorods formed from the triple-decker complex show good semiconductor feature.